A phase II study of panobinostat in patients with primary myelofibrosis (PMF) and post-polycythemia vera/essential thrombocythemia myelofibrosis (post-PV/ET MF). (February 2017) - Mascarenhas, John; Sandy, Lonette; Lu, Min; Yoon, James; Petersen, Bruce; Zhang, David; Ye, Fei; Newsom, Carrie; Najfeld, Vesna; Hochman, Tsivia; Goldberg, Judith D.; Hoffman, Ronald
Highlights: Phase II data of panobinostat in myelofibrosis demonstrates clinical activity. Panobinostat for myelofibrosis is effective in reducing spleen volume. Panobinostat requires prolonged low doses to observe clinical effect. Study of combination panobinostat and ruxolitinib for myelofibrosis is warranted. Abstract: Myelofibrosis is a chronic and progressive myeloproliferative neoplasm characterized by anemia, splenomegaly, debilitating symptoms and leukemic transformation. Ruxolitinib, an oral JAK1/2 inhibitor, is highly effective in ameliorating systemic symptoms and reducing splenomegaly. Current clinical research is focused on the evaluation of agents based on pre-clinical rationale that can result in disease course modification. Panobinostat is a pan-histone deacetylase inhibitor that has demonstrated clinical activity as a single agent in early phase trials of myelofibrosis. We previously conducted a phase I trial of panobinostat monotherapy in patients with myelofibrosis and determined 25 mg thrice weekly as the recommended phase II dose. We then completed an investigator initiated, Simon 2-stage, phase II trial of 22 myelofibrosis patients at our single institution. After 6 cycles of therapy, the overall response rate by IWG-MRT criteria was 36% (8/22; 95% CI: 16–56%). The median percent reduction in spleen volume was 34% (range, 1.6%–73%) in eight evaluable patients. The average reduction in JAK2V617F allele burden was 6.8% (Range; −4.0% to 20.2%) and one patient obtained a complete molecular response. Six patients remained on therapy in the extension phase for a median of 18 months (range, 7–44). Treatment discontinuation was frequent due to patient/physician perception of therapy ineffectiveness. The optimal dosing of panobinostat for the treatment of MF remains somewhat ill-defined but appears to be most effective and better tolerated when administered at lower doses over a prolonged duration of therapy.